Perilaku Agresi Orang Tua terhadap Anak di Kota Makassar Ditinjau dari Self Control dan Kemampuan Komunikasi - Aswar, Aswar; Pusadan, Faizal Ramadan (Esa Unggul University, 2021)
AbstractChildren are often forced to follow their parents' wishes, which often leads to aggressive behavior, so that self-control is needed to minimize aggression. This research uses a quantitative approach. The population of this research is all citizens of Makassar who are married and have children. Determination of the sample using the krejcie table and Morgan with a total sample of 384 respondents. Methods of data collection through questionnaires with a Likert scale model, and hypothesis testing with simple regression analysis. The results of the study showed a significant negative effect of self control and communication skills on the aggression behavior of parents towards children in the city of Makassar. With the magnitude of the coefficient of determination or R Square. From the data analysis, the R Square is 0.07 or equal to 7%. This figure means that self control (X1) and communication skills (X2) simultaneously (together) affect the aggressiveness of parents to children in Makassar City by 7%. While the remaining 93% is influenced by other variables not examined in this study. The partial effect of self control is -0.172 and communication ability is -0.128, the coefficient is negative, which means that there is a significant negative effect between self-control and communication skills on the aggressiveness of parents to children. It means that the increased self-control and communication skills of parents, the more able to reduce the aggression behavior of parents towards their children.